Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio as potential predictors of nosocomial infection in patients undergoing veno-arterial extracorporeal membrane oxygenation: A cohort study - Zishu Xu; Lu Qi; Shiqiong Su; Zhijing Xu; Yuan Geng; Yangang Shi; Congmei Wang; Jie Wu; Ruifang Liu (PLoS ONE, 2025)
Objective The aim of this study was to evaluate and compare the predictive value of the neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) for nosocomial infection in patients undergoing veno-arterial extracorporeal membrane oxygenation (VA-ECMO). Methods In this retrospective cohort study, we assessed 95 patients who underwent VA-ECMO between 2018 and 2023 at the Third People’s Hospital of Henan Province. The association between NLR, PLR and nosocomial infection in patients undergoing VA-ECMO was tested using logistic regression model. Results Among 95 VA-ECMO patients, 30 were found to have developed nosocomial infection (infection rate 31.58%). Patients with higher levels of NLR and PLR showed higher rates of nosocomial infections (p < 0.05). Higher NLR were associated with an increased risk of nosocomial infections in patients undergoing VA-ECMO (odds ratio [OR], 4.858; 95% confidence interval [95% CI], 1.864–12.663) (P = 0.001), after adjusting for sex, age, hemoglobin, albumin, and duration of VA-ECMO treatment. In reference to the first tertile of NLR, ORs were 6.931 (95% CI, 1.496–32.118) for the second tertile, 8.898 (95% CI, 1.943–40.751) for the third tertile. PLR was a risk factor for nosocomial infections in patients undergoing VA-ECMO (OR 5.478; 95%CI 2.117–14.176) after adjusting for traditional risk factors (P < 0.001). ROC curve analysis showed that the area under the curve (AUC) of NLR and PLR to predict nosocomial infections in patients treated with VA-ECMO were 0.710 and 0.763, respectively. Conclusions High NLR and PLR were associated with an increased risk of nosocomial infection in patients treated with VA-ECMO.